Internal Quality Assurance System Of Education In Financing Standards and Assessment Standards - Ainia Hidayah; Syahrani (CV. ADIBA AISHA AMIRA, 2022)
The important role of quality fulfillment in improving the internal quality of education, where the level of success of learning is strongly supported by the fulfillment of effective quality in accordance with the needs and conditions in the educational environment, education quality assurance, especially in education programs, is obliged to provide and provide assistance in meeting standards. Educational Assessment Standards are criteria regarding the mechanisms, procedures, and instruments for assessing student learning outcomes. Assessment standards by educators according to BSNP include general standards, planning standards, implementation standards, processing and reporting standards of assessment results and standards for the use of assessment results.